Analysis of the Negative Impact of Penalties Levied by the Peruvian Government on a Private Company in the Health Sector - Obando Vega, Anny Janeth (2023)
In this paper, the negative impact of purchase orders with penalties for a private company in the health sector with contracts with the Peruvian government is analyzed. The research question focuses on how to reduce the number of penalties, and the objective is to reduce logistical issues. Vester’s methodology and Ishikawa and Pareto diagrams were applied to prioritize problems and determine their causes and effects. It was found that failure to meet deadlines is the primary reason for the penalties levied by the government. Therefore, it is necessary to implement process improvement methodology in the Supply Area to reduce penalties, in order to ensure compliance with all contracts and as a consequence, achieve greater organizational profitability.